A STUDY ON ETIOLOGICAL FACTORS AND CO MORBIDITIES IN CHILDREN WITH SEVERE ACUTE MALNUTRITION ADMITTED IN A RURAL TERTIARY CARE CENTRE - V, SIVASHANKARI; K, NISHA; C, JAYACHANDRAN; K, BALAMURUGAN (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: In India, children under 5 years of age suffer from varying degrees of malnutrition. As the severity of undernutrition increases, risk of other diseases increases exponentially. The aim of this study was to identify etiological factors for severe acute malnutrition (SAM) in children aged 6 months to 5 years. Methods: This was a cross-sectional descriptive study conducted at Department of Pediatrics of a rural tertiary care center, Tamil Nadu, India, between January and December 2020. All children with SAM in the age group of 6 months to 5 years were included in the study while children with secondary causes of malnutrition were excluded. Sociodemographic data were entered in preformed proforma. Nutritional status was assessed using the World Health Organization (WHO) standard growth charts. Descriptive data were given in summary statistics while Student’s t-test and Pearson’s Chi-square test were used for analyzing variables. p<0.05 was considered statistically significant. Results: Among 111 children included, mean age was 25.2±15.7 months, 55.85% were females, mean height was 82.4±12.0 cm, 85.58% were from lower socioeconomic status, and mean duration of hospital stay was 5.9±2.5 days. Mothers were the caregivers in 80.18%, 63.96% were unaware of breastfeeding practices, and 59.46% had exclusively breastfed for <3 months. Complementary feed was unsatisfactory in 77.48%, and 75.67% of children were given cow’s milk but inadequate. As maternal age increased, awareness of breastfeeding (p=0.0005) and complementary feeding (p=0.0005) significantly increased. The mean weight at admission was 8.09±2.25 kg which increased to 8.26±2.25 kg and was significant (p=0.0005). Conclusion: As mothers were the primary caregivers but with poor awareness on breastfeeding practices, awareness campaigns targeting mothers will be more effective. As awareness on breastfeeding and complementary feeding increased with increasing maternal age, age of childbirth can be increased to more than 20 years.